The Natural Law Foundations of Modern Social Theory : a Quest for Universalism. - Chernilo, Daniel (Cambridge University Press, 2013)
Daniel Chernilo offers an original reconstruction of the history of universalism in modern social thought from Hobbes to Habermas.